HOXB7 drives bladder cancer progression via H-Ras/ERK signaling: a potential therapeutic target and prognostic biomarker - Chen, Xulong; Jiang, Kehua; Chen, Kun; An, Yu; Wang, Qing; Chen, Xiaolong; Zhang, Peng; Zhong, Quliang; Sun, Fa (Frontiers in Oncology, 2025)
BackgroundBladder cancer (BC) is a common malignancy characterized by high recurrence and poor prognosis. HOXB7, a member of the HOX gene family, is aberrantly expressed in various tumors, but its role in BC remains unclear.MethodsHOXB7 expression in BC was analyzed using public databases (GEPIA, UALCAN) and validated by immunohistochemistry on a tissue microarray of 36 BC patients. In vitro experiments using BC cell lines (5637 and T24) were conducted to investigate the effects of HOXB7 knockdown or overexpression on cell proliferation, apoptosis, migration, invasion, and epithelial–mesenchymal transition (EMT). Western blotting and rescue assays with ERK pathway modulators (Ro67–7476 and PD98059) were performed to assess the involvement of the H-Ras/Raf-1/MEK/ERK signaling cascade. Xenograft mouse models were employed to evaluate tumorigenicity in vivo.ResultsHOXB7 was significantly upregulated in BC tissues and cell lines, correlating with advanced tumor stage and poor overall survival. HOXB7 silencing inhibited BC cell proliferation, migration, invasion, and EMT, while promoting apoptosis. Conversely, HOXB7 overexpression produced the opposite effects. Mechanistically, HOXB7 activated the H-Ras/Raf-1/MEK/ERK pathway, as indicated by increased phosphorylation of MEK and ERK. These effects were reversed by pharmacological inhibition or activation of ERK signaling. In vivo, HOXB7 knockdown suppressed tumor growth and ERK pathway activation.ConclusionThis study provides the first comprehensive experimental evidence that HOXB7 drives BC progression via activation of the H-Ras/Raf-1/MEK/ERK pathway. These findings highlight HOXB7 as a potential prognostic biomarker and therapeutic target in BC. Furthermore, our results lay the foundation for future investigations into the broader molecular and immunological networks modulated by HOXB7 in BC.